2015
DOI: 10.1111/ijs.12451
|View full text |Cite
|
Sign up to set email alerts
|

Threshold for NIH Stroke Scale in Predicting Vessel Occlusion and Functional Outcome after Stroke Thrombolysis

Abstract: Ideally, all acute stroke patients should have immediate access to multimodal imaging. In reality these services are limited. Baseline National Institutes of Health Stroke Scale scores of 11 and 12 were identified as markers of baseline vessel occlusion and functional independency after intravenous thrombolysis, respectively. These values are time dependent; therefore, a threshold of National Institutes of Health Stroke Scale 9 or 10 points may be considered in the prehospital selection of patients for immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 23 publications
3
42
0
14
Order By: Relevance
“…Although a recent study showed a much lower FNR (12%) using the NIHSS score cutoff ≥11, 6 our results are in line with 2 previous studies in which FNRs of 23% and 35% were observed. 7,21 One may argue that the cutoffs maximizing the sum of sensitivity and specificity may not be optimal in the particular setting of LAO prediction because a high FNR has greater implications than a high FPR, as the former would lead to delaying time to reperfusion, whereas the latter would only lead to an increase in the workload of CSCs. Therefore, we attempted to identify an NIHSS score cutoff that would allow practitioners to reasonably rule out LAO but were unable to find one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a recent study showed a much lower FNR (12%) using the NIHSS score cutoff ≥11, 6 our results are in line with 2 previous studies in which FNRs of 23% and 35% were observed. 7,21 One may argue that the cutoffs maximizing the sum of sensitivity and specificity may not be optimal in the particular setting of LAO prediction because a high FNR has greater implications than a high FPR, as the former would lead to delaying time to reperfusion, whereas the latter would only lead to an increase in the workload of CSCs. Therefore, we attempted to identify an NIHSS score cutoff that would allow practitioners to reasonably rule out LAO but were unable to find one.…”
Section: Discussionmentioning
confidence: 99%
“…5 Several dedicated clinical scores, as well as National Institute of Health Stroke Scale (NIHSS) score cutoffs, have been proposed to help predict LAO in patients with suspected AIS and might be used for prehospital triage. [6][7][8] However, data on the predictive values of particular scores in independent populations is scarce, and the optimal NIHSS score cutoff for LAO prediction varies greatly across studies, ranging from 6 to 14. 8,9 Although a recent European consensus statement suggested that if baseline arterial imaging is not available, an NIHSS score ≥9 points (within 3 hours of stroke onset) or ≥7 points (within 6 hours) may indicate LAO, 2 current US and Canadian guidelines do not state a clinical score as useful to predict LAO.…”
mentioning
confidence: 99%
“…In such cases, determining emergent large vessel occlusion from the baseline National Institutes of Health Stroke Scale is imperfect; however, the cut off of 12 was conservative (positive predictive value 64%). 8 It is difficult to anticipate future practice evolution. This study was based on average time metrics (door-to-needle and door-to-reperfusion) assuming futile reperfusion beyond 7 hours, but some may benefit beyond this after selection by multimodal imaging.…”
Section: May 2016mentioning
confidence: 99%
“…The association between higher baseline NIHSS and the presence of vessel occlusion was recently shown in another publication from our group. 25 The importance of future studies separately investigating the association between score prediction and outcome after endovascular thrombectomy is evident.…”
Section: Strokementioning
confidence: 99%